Comparative Analysis of Liquidity Ratios in the Renewable Energy Subsector - Achmad Fawaid; Siti Nur Azizatul Luthfiyah; Slamet Wijiono; Muhammad Rizky Prima Sakti; Mohd Shahid Mohd Noh (Institut Teknologi dan Sains Mandala, 2026)
This study aims to analyze the financial performance of PT Pertamina Geothermal Energy Tbk and PT Alamtri Resources Indonesia Tbk during the 2021-2025 period using a liquidity ratio approach including the Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (ChR). The research method used is a quantitative method with secondary data obtained from the company's financial statements published through the Indonesia Stock Exchange (IDX) and annual reports. The data analysis technique is carried out by calculating and comparing the liquidity ratio values ​​between the this companies during the 2021-2025 period. The research results show that PT Alamtri Resources Indonesia Tbk's liquidity performance is excellent and continues to improve annually. A slight decline occurred in 2023, but significant progress has been made. Meanwhile, PT Pertamina Geothermal Energy is generally performing well, with excellent ratings across all its ratios. Despite a decline in 2022, the company has managed to achieve a strong and sustainable recovery through 2025. This study recommends that the two companies maintain their excellent liquidity performance going forward to avoid a downgrade in their financial performance rating.